Impatiens walongensis (Balsaminaceae), a new species from North-East India - Hareesh, Vadakkoot Sankaran; Borah, Souravjyoti; Sabu, Mamiyil (Phytotaxa, 2017)
Impatiens walongensis is described from Anjaw district of Arunachal Pradesh, North-East India. Detailed descriptions, distribution, and ecology along with colour photographs are provided.